Fidalgos and miles Christi. Borderless lives in medieval Hispania - Sottomayor-Pizarro, José Augusto de (2022)
This article is a result of the research project Transferencias humanas, culturales e ideológicas entre los reinos ibéricos (siglos XIII-XV), financed by the Ministerio de Economía, Industria y Competitividad (HAR2017-89398-P) and coordinated by Doutora Isabel Beceiro Pita (Instituto de Historia-CSIC). Based on the importance of the Luso-Castilian border in the context of medieval Hispania and its complexity as a political construction, the objective of this reflection is to assess its impact at the level of manorial groups, either secular or ecclesiastical. The way how these social groups had interpreted the frontier is a central issue for this study. Fidalgos and miles Christi, usually called knights in simple terms, had traced similar tendencies for understandable reasons. Fidalgos and miles Christi were part of the medieval elites that boosted the peninsular exchanges, developing frequent trajectories over borders in medieval Hispania. The aristocracy and the friars of the Military Orders, in particular, those from the international Orders, had a very fluid conception of the frontier, to which family and institutional interests were superimposed. The noblemen found in the border crossing a natural mechanism to circumvent some political problems, arising from conflicts with monarchs, or to materialize strategies of power of some lineages with patrimonies constituted long before the creation of the kingdom of Portugal itself. In turn, the friars of the Military Orders were sometimes members of these families, imbued with non-border behaviors, which were reinforced when they professed in multinational institutions, not overlapping with the delimitations of the political and diplomatic border.   Bibliography Sources Handwritten sources Lisboa, Torre do Tombo, Chancelaria de D. Dinis, lv. 3. Lisboa, Torre do Tombo, Gaveta VI, mç. único, nº 29. Lisboa, Torre do Tombo, Gaveta XII, mç. 1, nº 4. Lisboa, Torre do Tombo, L.N., Extras. Lisboa, Torre do Tombo, L.N., Guadiana, lv. 1. Lisboa, Torre do Tombo, Mosteiro de Santa Maria de Almoster, cx. 7, mç. 2, nº 40. Lisboa, Torre do Tombo, Mosteiro de Santos-o-Novo, cx. 1, mç. 2, nº 6.  Printed sources AZEVEDO, Pedro A. de; FREIRE, A. Braamcamp – Livro de D. João de Portel, edição fac-simile coordenada por Hermenegildo Fernandes. Lisboa: Edições Colibri e Câmara Municipal de Portel, 2003. COSTA, Avelino de Jesus da – Álbum de Paleografia e Diplomática, 4ª ed., Coimbra, 1983. COSTA, Avelino de Jesus da; MARQUES, Maria Alegria Fernandes – Bulário português de Inocêncio III (1198-1216). Coimbra: Instituto Nacional de Investigação Científica, 1989. Livro dos forais, escripturas, doações, privilégios e inquirições, com um estudo de José Mendes da Cunha Saraiva, Subsídios para a História da Ordem de Malta, II-IV, 3 vols., separata de “Ocidente”, vols. 25-28. Lisboa: Arquivo Histórico do Ministério das Finanças, 1946-48. MARQUES, José – Liber Fidei Sanctae Bracarensis Ecclesiae. Reedição melhorada e ampliada, 2 tomos. Braga: Arquidiocese de Braga, 2016. VENTURA, Leontina; OLIVEIRA, António Resende de (eds.) – Chancelaria de D. Afonso III, Livro I. Vol. 2. Coimbra: Imprensa da Universidade, 2006. Studies AYALA MARTÍNEZ, Carlos de – “Frontera Castellano-Portuguesa y Órdenes Militares. Problemas de jurisdición (ss. XII-XIII)”. In ÁLVAREZ PALENZUELA, Vicente (ed.), Jornadas de Cultura Hispano-Portuguesa. Madrid: Universidad Autónoma de Madrid, 1999, pp. 51-92. CALDERÓN MEDINA, Inés – Cum magnatibus regni mei. La nobleza y la monarquía leonesas durante los reinados de Fernando II y Alfonso IX de León (1157-1230). Madrid: CSIC, 2011. CALDERÓN MEDINA, Inés – Los Soverosa: una parentela nobiliaria entre tres reinos. Poder y parentesco en la Edad Media Hispana (ss. XI-XIII). Valladolid: Ediciones Universidad de Valladolid, 2018. CALDERÓN MEDINA, Inés – “Reyes, nobles y frontera. Entre la violencia y el parentesco en el espacio fronterizo galaico portugués (siglos XII-XIII)”. Cuadernos de Estudios Gallegos 64/130 (2017), pp. 91-117. CALDERÓN MEDINA, Inés; FERREIRA, João Paulo Martins – “Beyond the Border: The Aristocratic mobility between the kingdoms of Portugal and León (1157-1230)”. e-JPH [online] 12/1 (2014), pp.1-48. [Consultado a 3 Maio 2020]. Disponível em https://www.brown.edu/Departments/Portuguese_Brazilian_Studies/ejph/html/issue23/html/v12n1a01.html. CALDERÓN MEDINA, Inés; FERREIRA, João Paulo Martins – “Os senhores de Cabreira e Ribeira. Um estudo sobre a sua origem e transcendência peninsular. Séculos XII- XIV”. Revista Portuguesa de História 44 (2013), pp. 123-152. COSTA, Paula Pinto – “Álvaro Gonçalves Pereira: um homem entre a oração e a construção patrimonial como estratégia de consolidação familiar”. População e Sociedade 23 (Junho 2015), pp. 45-71. [Consultado a 3 Maio 2020]. Disponível em http://www.cepesepublicacoes.pt/portal/pt/obras/populacao-e-sociedade-n-o-23 . COSTA, Paula Pinto – “De la frontière a la consolidation du territoire: la contribution des Ordres militaires au processus de territorialisation aux XIIe-XIIIe siecles”. In BOISSELLIER, Stéphane; FERNANDES, Isabel Cristina (eds.) – Entre Islam et Chrétienté. La territorialisation des frontières, XIe-XVIe siècles. Rennes: Presses Universitaires de Rennes, 2015, pp. 141-169. COSTA, Paula Pinto – “História da Comenda. Comenda e território. A dimensão imaterial da comenda de Marmelar”. In FONSECA, Luís Adão da (coord.) – Comendas das Ordens Militares: perfil nacional e inserção internacional. Noudar e Vera Cruz de Marmelar. Coleção Militarium Ordinum Analecta. Vol. XVII. Porto: CEPESE e Fronteira do Caos, 2013, pp. 207-234. COSTA, Paula Pinto – “Reflexos em Portugal de um ‘mundo’ em mudança: a origem da ordem de Cristo no século XIV”. In GUINOT, Enric; ANDRÉS, Fernando; CERDÁ, Josep; PARDO, Juan F. (eds.) – Santa María de Montesa. La Orden Militar del Reino de Valencia. Siglos XIV-XIX. Valencia: P.U.V., 2019, pp. 73-87. COSTA, Paula Pinto – Templários em Portugal. Homens de Religião e de Guerra. Lisboa: Manuscrito, 2019. CUNHA, Maria Cristina Almeida e – A Ordem Militar de Avis (das origens a 1329). Porto: Universidade do Porto, 1989. Dissertação de Mestrado. CUNHA, Maria Cristina Almeida e – “A eleição do Mestre de Avis nos séculos XIII-XV”. Revista da Faculdade de Letras – História XIII (1996), pp. 103-109. CUNHA, Maria Cristina Almeida e – “A filiação da Ordem de Avis em Calatrava. Algumas notas a propósito da visita de 1346”. In As Ordens Militares e de Cavalaria na Construção do Mundo Ocidental - Actas do IV Encontro sobre Ordens Militares. Lisboa: Edições Colibri e Câmara Municipal de Palmela, 2005, pp. 317-326. CUNHA, Mário Raul – A Ordem Militar de Santiago: das origens a 1327. Porto: Universidade do Porto, 1991. Dissertação de Mestrado. FERREIRA, João Paulo Martins – Entre a Consanguinidade e a Naturalidade: A Movimentação da Nobreza Portuguesa entre os Reinos de Portugal e Leão (1157-1230). Porto: Universidade do Porto. Dissertação de Mestrado. FERREIRA, João Paulo Martins – A Nobreza Galego-Portuguesa da Diocese de Tui (915-1381). Santiago de Compostela: CSIC, 2019. FERREIRA, João Paulo Martins – “Organização Diocesana. A Influência Transfronteiriça das Dioceses de Braga e Tuy e a Génese de Portugal”. In FONSECA, Luís Adão da (coord.) – Entre Portugal e a Galiza. Um olhar peninsular sobre uma região histórica. Porto: CEPESE e Fronteira do Caos, 2014, pp. 189-194. FONSECA, Luís Adão; et al. – “Bragança na Idade Média”. In SOUSA, Fernando de (coord.) – Bragança. Das Origens à Revolução Liberal de 1820. Vol. I. Bragança: Município de Bragança, CEPESE, 2019, pp. 187-380. LÓPEZ FERNÁNDEZ, M. – Pelay Pérez Correa: Historia y Leyenda de un maestre santiaguista. Badajoz: Diputación de Badajoz, 2010. MARQUES, José – “Os Castelos Algarvios da Ordem de Santiago no Reinado de D. Afonso III”. Caminiana 13 (Dezembro de 1986), pp. 9-32. MATTOSO, José – D. Afonso Henriques. Lisboa: Círculo de Leitores, 2006. MOREIRA, Filipe Alves – “O Papel da Língua e do Bilinguismo”. In FONSECA, Luís Adão da (coord.) – Entre Portugal e a Galiza. Um olhar peninsular sobre uma região histórica. Porto: CEPESE e Fronteira do Caos, 2014, pp. 381-383. ROSAS, Lúcia – “A Lição dos Mosteiros nas Margens do Rio Minho. A perspectiva portuguesa”. In FONSECA, Luís Adão da (coord.) – Entre Portugal e a Galiza. Um olhar peninsular sobre uma região histórica. Porto: CEPESE e Fronteira do Caos, 2014, pp. 279-281. SILVA, Luísa Morgado de Sousa e – “A Ordem de Cristo durante o mestrado de D. Lopo Dias de Sousa (1373?-1417)”. In Militarium Ordinum Analecta. Vol. I. Porto: Fundação Eng.º António de Almeida, 1997, pp. 5-126. SOTTOMAYOR-PIZARRO, José Augusto de – “A Aristocracia no Território de Bragança (Séculos XI-XV). O Tempo dos Bragançãos (Sécs. XI-XIII)”. In SOUSA, Fernando de (coord.) – Bragança. Das Origens à Revolução Liberal de 1820. Vol. I. Bragança: Município de Bragança, CEPESE, 2019, pp. 192-208. SOTTOMAYOR-PIZARRO, José Augusto de – “As Ordens Militares e a Centralização Régia Portuguesa (Sécs. XII-XV) – algumas reflexões”. In VIII Encontro sobre Ordens Militares. Ordens Militares, Identidade e Mudança (Palmela, 12 a 16 de Junho de 2019). Actas (no prelo). SOTTOMAYOR-PIZARRO, José Augusto de – “De e Para Portugal. A Circulação de Nobres na Hispânia Medieval (Séculos XII a XV)”. Anuario de Estudios Medievales 40/2 (julio-diciembre de 2010), pp. 889-924. SOTTOMAYOR-PIZARRO, José Augusto de – Linhagens Medievais Portuguesas. Genealogias e Estratégias (1279-1325), 3 volumes. Porto: CEGHHF, 1999. SOTTOMAYOR-PIZARRO, José Augusto – “«Pela Morte se Conhece um Pouco da Vida». A propósito do testamento de Dona Châmoa Gomes de Tougues, fundadora do mosteiro de Santa Clara de Entre-os-Rios”. In Carlos Alberto Ferreira de Almeida. In Memoriam. Vol. II. Porto: Faculdade de Letras da Universidade do Porto, 1999, pp. 219-233.